Pengaruh Literasi Keuangan, Lifestyle, dan Sikap Keuangan Terhadap Perilaku Keuangan Mahasiswa di Universitas Mega Buana Palopo - Silvira Silvira; Samsul Bachri; Duriani Duriani (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the influence of financial literacy, lifestyle, and financial attitudes on the financial behavior of students at Universitas Mega Buana Palopo. The background of this research is the growing trend of consumptive and hedonistic lifestyles driven by social media and the convenience of online shopping, which often results in less optimal financial management among students. The research method employs a quantitative approach with respondents consisting of students from Universitas Mega Buana Palopo who come from diverse economic backgrounds and demonstrate a high level of technology utilization. The independent variables in this study include financial literacy, lifestyle, and financial attitudes, while the dependent variable is students’ financial behavior. The literature review indicates that financial literacy, lifestyle, and financial attitudes significantly influence financial behavior. A sound understanding of financial concepts, a controlled lifestyle, and disciplined as well as responsible attitudes are key factors in shaping healthy financial behavior among students. The results of the discussion show that financial literacy and financial attitudes have a positive and significant contribution to forming healthy financial behavior, where a good understanding of financial concepts and a disciplined attitude help students manage budgets more systematically. Conversely, lifestyle was found to have no significant effect on the financial behavior of students at Universitas Mega Buana Palopo. This is presumably because the average income of students is at a similar level, leading them to prioritize essential needs over personal desires or mere lifestyle trends. Simultaneously, financial literacy, lifestyle, and financial attitudes contribute 87.2% to students' financial behavior. This research is expected to support the improvement of literacy and personal financial management in higher education institutions.